1992
DOI: 10.1071/ch9921903
|View full text |Cite
|
Sign up to set email alerts
|

The X-Ray Crystal-Structure of (+/-)-Pandamarine, the Major Alkaloid of Pandanus-Amaryllifolius

Abstract: The structure (2) of ( �)-pandamarine , the major alkaloid isolated from the leaves of Pandanus amaryllifolius Roxb., has been determined by an X-ray diffraction study. Diffractometer data at 295 K were refined by least-squares techniques to a residual of 0.049 2244 'observed' reflections). Crystals of (2) are triclinic, P1, a 13.077(2), b 9.857(5), c 7.214(2) �, α 106.91(3), β 96.22(2), γ 100.01(2)0, Z 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…2 Biogenetically, the isolation team have proposed that pandamarine (1) might be the spiro-N,N-ketalization product of a symmetric bis-lactam (3, Scheme 1). 1,3 This proposal is consistent with the fact that pandamarine (1) occurs as a racemate. It was suggested that this possible biogenetic intermediate 3 might in turn be obtained from (2S)-4-hydroxy-4-methylglutamic acid (4, Scheme 1) since this amino acid was found in a related species, P. veitchii.…”
supporting
confidence: 85%
See 3 more Smart Citations
“…2 Biogenetically, the isolation team have proposed that pandamarine (1) might be the spiro-N,N-ketalization product of a symmetric bis-lactam (3, Scheme 1). 1,3 This proposal is consistent with the fact that pandamarine (1) occurs as a racemate. It was suggested that this possible biogenetic intermediate 3 might in turn be obtained from (2S)-4-hydroxy-4-methylglutamic acid (4, Scheme 1) since this amino acid was found in a related species, P. veitchii.…”
supporting
confidence: 85%
“…Pandamarine (1, Scheme 1) is an alkaloid that was isolated in 1992 by Byrne's group from the leaves of the tropical plant Pandanus amaryllifolius. 1 Pandamarilactone-1 (2, Scheme 1), was also isolated from the same plant one year later. 2 Biogenetically, the isolation team have proposed that pandamarine (1) might be the spiro-N,N-ketalization product of a symmetric bis-lactam (3, Scheme 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[ 1 - 3 ] The corresponding aza-spiroketal (cf: general structure B ) containing natural products, while less common, are also found in plants, shellfish and microbes. [ 4 , 5 ] For example, pandamarilactone-1 and pandamarine were isolated from the leaves of Pandanus amaryllifolius ;[ 6 ] solasodine and its derivatives were isolated from Solanum umbelliferum , which exhibited significant activity toward DNA repair-deficient yeast mutants;[ 7 ] azaspiracids are marine phycotoxins isolated from cultivated mussels in Killary harbor, Ireland;[ 8 ] and chlorofusin A is a novel fungal metabolite showing the potential as a lead in cancer therapy. [ 9 ] In addition, aza-spiropyrans C , being able to equilibrate with the corresponding non-spiro analogue D , is a well known class of compounds possessing photochromic properties for use in the area of photochemical erasable memory,[ 10 ] and also found applications as self-development photography, actinometry, displays, filters, lenses of variable optical density,[ 11 ] and photomechanical biomaterials etc.…”
Section: Introductionmentioning
confidence: 99%